Sustainability Marketing Tourism pada Kampung Wisata - Mega Mirasaputri Cahyanti; Wachidatuz Zuhria Iliyawati (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2018)
This study aims to determine the effect of the concept of green marketing to influence tourists' intentions to avoid future damage for new rural tourism. Meanwhile, quantitative research method used in this research, and also this research type was descriptive research, sampling technique used was incidental purposive sampling that was tourists on rural tourism like â€œKampung Wisata in Malangâ€ as much as 200 tourists. Analysis technique using regression analysis. The result of this research was green product, green promotion, people, price, and physical evidence had significant effect to intention to maintain the sustainability of rural tourism. But procedure and place had no significant effect to intention to maintain the sustainability of rural tourism. Research implications was that the managers of â€œKampung Wisataâ€ add the tourism agenda related to environmental sustainability, the use of promotional media that was eco-green, increasing the involvement of local residents and adding facilities related to environmental sustainability.